Activated Carbon Derived From OPEFB by One Step Steam Activation and Its Application for Dye Adsorption : Kinetics and Isothermal Studies - Fahriya Puspita Sari; Dede Heri Yuli Yanto; Gustan Pari (Dept. of Chemical Engineering, Diponegoro University, 2019)
Activated carbon was prepared from OPEFB by one step steam activation method. The adsorption performance for the removal of acid orange 52 (AO 52), reactive blue 19 (RB 19), basic violet 1 (BV 1) was investigated. Each dye has a different chemical structure such as azoic, anthraquinone, triarylmethane for AO 52, RB 19, and BV 1 respectively. The effects of adsorbent dosage, pH, and contact time on the adsorption process were studied. Experimental data were analyzed by model equations such as Langmuir, Freundlich and Temkin isotherms and it was found that the Langmuir isotherm model best fitted for all three dyes with R2 values is higher than 0.95. Langmuir model assumes a homogeneous nature and monolayer coverage of dye molecules at the outer surface of activated carbon. Adsorption kinetics was determined using pseudo-first-order, pseudo-second-order rate equations, Elovich model and also intraparticle diffusion models. Kinetic studies showed that the pseudo-second-order kinetic model better described the adsorption process with R2 values exceeds 0,99 compared with the other kinetics model. The SEM images showed AC pores was well developed with steam activation while wider porosity is created in the macropore range. FT-IR analysis had shown that the AC functional groups were disappeared because of vaporization the volatile materials when the heating process. Keywords: Activated Carbon, Adsorption Isotherms, Kinetic, OPEFB, Steam Activation